2015
DOI: 10.1890/14-1687.1
|View full text |Cite
|
Sign up to set email alerts
|

How functional traits, herbivory, and genetic diversity interact inEchinacea: implications for fragmented populations

Abstract: Habitat fragmentation produces small, spatially isolated populations that promote inbreeding. Remnant populations often contain inbred and outbred individuals, but it is unclear how inbreeding relative to outbreeding affects the expression of functional traits and biotic interactions such as herbivory. We measured a suite of 12 functional traits and herbivore damage on three genotypic cross types in the prairie forb, Echinacea angustifolia: inbred, and outbred crosses resulting from matings within and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 85 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…sponhemica from fragmented populations, found that most population trait means were significantly related to climate gradients, suggesting adaptive genetic differentiation in quantitative traits (see also Weber and Kolb, 2014; Ye et al, 2014). Likewise, Kittelson et al (2015) found that inbreeding significantly affected the expression of 12 functional traits in populations of the prairie forb Echinacea angustifolia , and Mannouris and Byers (2013) found a significant effect of genetic drift load on populations of Chamaecrista fasciculata from small fragments. In our study, lack of population differentiation in functional traits suggests a low impact of genetic drift and inbreeding on plant traits, and/or similar selective pressures acting on our populations due to similar microclimatic conditions (see also Ellmer et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…sponhemica from fragmented populations, found that most population trait means were significantly related to climate gradients, suggesting adaptive genetic differentiation in quantitative traits (see also Weber and Kolb, 2014; Ye et al, 2014). Likewise, Kittelson et al (2015) found that inbreeding significantly affected the expression of 12 functional traits in populations of the prairie forb Echinacea angustifolia , and Mannouris and Byers (2013) found a significant effect of genetic drift load on populations of Chamaecrista fasciculata from small fragments. In our study, lack of population differentiation in functional traits suggests a low impact of genetic drift and inbreeding on plant traits, and/or similar selective pressures acting on our populations due to similar microclimatic conditions (see also Ellmer et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In small habitat patches, plant inbreeding may occur more frequently as population sizes diminish (Honnay et al, 2005;Leimu et al, 2010). Inbred plants may have altered nutritional quality and defensive responses (Ridley et al, 2011;Kittelson et al, 2015). Therefore, plant inbreeding has the potential to alter herbivore performance (Hull-Sanders and Eubanks, 2005).…”
Section: Bottom-up Mechanismsmentioning
confidence: 99%
“…More recently, Kittelson et al . () found numerous physiological differences among plants attributable to genotypic class, including lower photosynthetic rates, water use efficiencies, and specific leaf areas, as well as higher trichome numbers, % C and % N of inbreds compared to outbred individuals. The abundance of aphids in the year of that study was too low to detect associations with these plant attributes.…”
Section: Discussionmentioning
confidence: 99%